Monitoring, Cash Holdings and Earnings Management: Evidence from U.S. Local Newspaper Closures - Iyad Almamlouk (2024)
This thesis, through its three essays, investigates the impacts of local newspaper closures on corporate behaviour, specifically focusing on corporate cash holdings and earnings management in the United States. Employing a difference-in-differences approach, the study analyses hand-collected data on the staggered closures of 44 local newspapers from 1986 to 2021 across 43 counties. The research reveals that these closures act as exogenous shocks, undermining the corporate monitoring function and exacerbating information asymmetry and agency conflicts, which lead firms to increase cash holdings and engage in earnings management. The first essay highlights that reduced media scrutiny prompts firms to hoard cash, with corporate governance scores and institutional shareholders mitigating these effects, while CEO pay gaps exacerbate them. The findings indicate that without the oversight of local newspapers, managers are more likely to prioritise personal gains over shareholders' interests, leading to an increase in cash reserves. This behaviour underscores the importance of robust corporate governance mechanisms in maintaining financial discipline. The second essay demonstrates that the absence of local newspapers worsens information asymmetry, causing firms to hold more cash as a defensive measure. The study finds a significant positive correlation between local media closures and increased cash holdings, particularly in firms with higher bid-ask spreads, indicating heightened information asymmetry. Financial analysts and short-term borrowing moderate these consequences by promoting cash distribution and dividend payouts. The presence of analysts and strategic borrowing acts as a counterbalance to the negative effects of reduced media coverage, ensuring better financial management practices. The third essay reveals a significant rise in accrual-based and real earnings management following newspaper closures, particularly in high-profile firms and those in financial distress. The absence of media oversight encourages managers to manipulate financial statements more frequently, leading to increased earnings management. The research utilises robust empirical methods, including placebo tests, propensity score matching, and instrumental variables like broadband and Craigslist entry, to address endogeneity concerns and validate the findings. By controlling for local economic conditions and employing a rigorous methodology, the study provides strong evidence of the causal relationship between newspaper closures and corporate financial practices. Overall, the study underscores the irreplaceable role of local newspapers as external governance mechanisms, highlighting the need for policies that support sustainable local media to ensure corporate accountability and financial transparency. The findings provide critical insights for policymakers, corporate managers, and investors on the importance of preserving local journalism in maintaining effective corporate governance and mitigating agency conflicts. Additionally, the research highlights the rise of digital media and its inability to fully replace the comprehensive role of traditional local newspapers in promoting ethical business practices. The emergence of news deserts, areas lacking sufficient local news coverage, further underscores the necessity for continued support and innovation in media practices to uphold the principles of good governance in an evolving media landscape.